PENGEMBANGAN MODEL MANAJEMEN KONFLIK DALAM PENANGANAN BULLYING DI SEKOLAH DASAR - Hasanah, Hosniyatul; Fadila, Putri Nur; Januarta, Ahmad Ananda Azka; Firmansyah , Alfan Roni; Mu'alimin, Mu'alimin (MPI STAI Sangatta Kutai Timur, 2024)
Conflict reflects differences, conflicts, or inconsistencies between interrelated elements, which can have positive (functional) or negative (dysfunctional) impacts. In the context of bullying, conflict management includes steps to overcome bullying behavior that often occurs in elementary schools. This study aims to develop a conflict management model based on a therapeutic approach and character values in handling bullying in elementary schools. The study used a literature study method with data collection techniques through borrowing books from the library, reviewing journal articles, and recording and processing data from relevant literature. The main findings of this study are the development of a model consisting of four stages: (1) Conflict Identification, which involves early detection of bullying through surveys and observations; (2) Mediation by Teachers, with the application of a dialogic approach and restorative-based resolution; (3) Character Education, through the integration of anti-bullying values in the curriculum; and (4) Collaboration between Parents and Schools, to strengthen emotional support and consistency of rules at home and school. This model is implemented through case simulations, teacher training, and workshops involving students and parents. The analysis results show that this approach can create a more inclusive environment, encourage positive behavioral changes, and minimize dysfunctional conflicts in elementary schools. The study recommends the wider application of this model with the support of government policies and the development of the capacity of educators.